On machining of hard and brittle materials using rotary tool micro-ultrasonic drilling process. Issue 7 (19th May 2019) - Kumar, Sandeep; Dvivedi, Akshay
ABSTRACT: The present paper reports on a recently developed rotary tool micro-ultrasonic drilling (RT-MUSD) process. The RT-MUSD process was utilized for machining of micro-holes in zirconia, silicon and glasswork materials. The effects of work material properties on the performance characteristics (material removal rate (MRR), depth of hole and hole overcut) of RT-MUSD process were investigated by varying the power rating, rotation speed, abrasive size and slurry concentration. Additionally, machined micro-holes and tool surface were analyzed considering microscopic images. The experimental results revealed that the MRR and depth of hole increased by increasing the power rating. An increase in rotation speed up to 300 rpm, abrasive size up to #1200 mesh and concentration up to 20% increased the MRR, depth of hole and decreased hole overcut. The maximum machining rate and hole overcut were observed during machining of silicon followed by glass and zirconia. The fracture toughness and hardness of the work material affected the MRR and tool wear, respectively. Pure brittle fracture mode of material removal was observed in all the work materials during RT-MUSD process. Eventually, the RT-MUSD process was optimized using desirability approach and a micro-hole of depth 4355 µm was achieved using optimal parameter settings.